Investment and the Optimal Idleness of Capital - Winston, Gordon C.; McCoy, Thomas O. (Review of Economic Studies, 1974)
Gordon C. Winston, Thomas O. McCoy; Investment and the Optimal Idleness of Capital12, The Review of Economic Studies, Volume 41, Issue 3, 1 July 1974, Page